IMPLEMENTASI PENGELOLAAN MASJID AL-MUHAJIRIN DALAM MEMAKMURKAN MASJID - Caniago, Fauzi (LPPM Politeknik Pajajaran ICB, 2023)
The implementation of management in prospering the mosque is considered necessary to be applied in every mosque because we often find a mosque that is less productive that cannot answer the needs of the ummah and therefore the importance of an active, innovative and productive management so that the mosque can attract people to worship closer to Allah SWT. The mosque is a sacred place for Muslims that functions as a place of worship, the centre of religious activities, and the community is developed in a regular and planned manner. This research uses a descriptive qualitative approach that aims to examine the ongoing or natural situation at the time of contact with the mosque. The findings show that: 1. The implementation of the management of the Al-Muhajirin mosque in the field of Idarah has not gone well where the mosque management rarely holds meetings, even though it is very important to establish good communication between administrators so that activities can run as expected. 2. The implementation of Al-Muhajirin Mosque Management in the Imarah field has not been running optimally, including the activity programme only touching on short-term planning, while planning activities in the long term there is no mature planning made by the management. 3. The implementation of Al-Muhajirin Mosque Management in the field of Ri'ayah has not gone well where the dirty mosque facilities are not well maintained. Good mosque management requires accurate management implementation so that the mosque becomes prosperous.